Multinational Corporations and the Socio-Economic Unrest in the Niger-Delta Region of Nigeria - Adekunle Alaye (International Studies Journal)
The focus of this study is to address the challenges and impacts of multinational corporations on the socio economic development of the Niger-Delta region of Nigeria. Indeed the region and Nigeria in general has been very much affected by the deleterious activities of the multinational corporations, operating in the country. Their abhorrent acts have affected her economy immensely and has inspired unrest in some parts of the country, particularly the Niger-Delta region of Nigeria which host most of the major multinational corporations from different parts of the world.The activities of multinational corporations have been identified as questionable or even unethical because of the harms they have caused the society. In the oil sector for example, which of course is the economic mainstay in Nigeria, these corporations perpetrate heinous activities such as pollution of the environment, inadequate technology transfer, violation of human rights, blunt refusal to discharge their social responsibilities, gas flaring which destroys wildlife, seafood’s and farmland especially in the Niger-Delta region without adequate compensation.